2022
DOI: 10.3389/fneur.2022.952493
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and clinical features of cerebellar ataxia with RFC1 biallelic repeat expansions in Japan

Abstract: The recessive intronic pentanucleotide repeat AAGGG expansion of replication factor complex subunit 1 (RFC1) is associated with cerebellar ataxia, sensory neuropathy, and vestibular areflexia syndrome. And the clinical spectrum has been continuously expanding. We conducted this study to demonstrate the clinical and genetic features of a large-scale case series of Japanese patients with cerebellar ataxia with RFC1 repeat expansions. We examined 1,289 Japanese patients with cerebellar ataxia and analyzed RFC1 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Subsequently, the remaining undiagnosed patients without a family history of autosomal dominant inheritance were screened for RFC1 repeat expansions. The detailed workflow has been described previously, 8 , 9 and the study flowchart is shown in Figure 1A . Age of onset distribution in our cerebellar ataxia cohort are summarized in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the remaining undiagnosed patients without a family history of autosomal dominant inheritance were screened for RFC1 repeat expansions. The detailed workflow has been described previously, 8 , 9 and the study flowchart is shown in Figure 1A . Age of onset distribution in our cerebellar ataxia cohort are summarized in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…In Japan, approximately 73% of patients with hereditary ataxia, including late‐onset cerebellar ataxia, remain undiagnosed. 8 Based on recent advancements, we conducted a thorough analysis of the FGF14 GAA repeat expansion using a diagnostic strategy integrating long‐range polymerase chain reaction (LR‐PCR), repeat‐primed PCR (RP‐PCR), and long‐read sequencing using Oxford Nanopore Technology platforms. We successfully identified FGF14 pathogenic repeat expansions from 12 patients who exhibited remarkable clinical variability.…”
Section: Introductionmentioning
confidence: 99%
“…Genetically undiagnosed younger onset cases were also included because such cases have been reported as positive for RFC1 expansions. 13 - 15 In addition, the growing number of studies performed thus far on this relatively recently described disease indicated an expansion of the phenotypic spectrum and the genetic heterogeneity, which possibly remain not fully elucidated. 10 , 12 , 13 , 15 , 26 - 30 Therefore, we cannot exclude the possibility of identifying positive younger-age cases.…”
Section: Discussionmentioning
confidence: 99%
“… 13 - 15 In addition, the growing number of studies performed thus far on this relatively recently described disease indicated an expansion of the phenotypic spectrum and the genetic heterogeneity, which possibly remain not fully elucidated. 10 , 12 , 13 , 15 , 26 - 30 Therefore, we cannot exclude the possibility of identifying positive younger-age cases. Ten out of 194 patients tested (5.2%) have been diagnosed with the pathogenic AAGGG repeat expansion in a homozygous state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation